The Influence of Core Values of BER-AKHLAK, Work Facilities and Work- Life Balance on Employee Commitment with Mental Well-Being As An Intervening Variable in the Administrative Bureau of the Leadership of the Regional Secretariat of East Java Province - Anugerah Aldiandra Kusuma; Siti Mujanah (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to analyze the influence of core values of Morality, work facilities, and work- life balance on employee commitment, with mental well-being as a mediating variable. This study was conducted on employees in the Administrative Bureau of the Leadership of the Regional Secretariat of East Java Province using a quantitative approach. Data was collected through a questionnaire of 50 respondents and analyzed using regression tests and Sobel Test to test the mediation effect. The results of the study show that the core values of Ber-Akhlak in work, work facilities, and work-life balance have a positive and significant influence on mental well-being. In addition, mental well-being has a significant influence on employee commitment and mediates the relationship between the three independent variables and employee commitment. Work facilities provide the greatest mediation influence compared to the core values of Moral Character and Work-Life Balance, emphasizing the importance of the role of leaders in supporting the mental welfare of employees in carrying out their work. This finding gives implications that the Administrative Bureau of the Leadership of the Regional Secretariat of East Java Province can increase employee commitment by implementing the core value policy of Ber-Akhlak, supporting work-life balance, and strengthening work facilities. This research also contributes to the human resource management literature by offering a new perspective in supporting employee mental well-being as a strategic factor in increasing organizational loyalty.